Simulasi Hidrologi dan Hidraulik Banjir di Lembah Anai: Studi Kasus 11 Mei 2024 - Syofyan, Elvi Roza; Herdianto, Revalin; Arlis, Angga Putra; Yuwono, Waluyo; Thaariq, Ath (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2025)
Since early 2023, Mount Marapi has shown its activity, even until 2024 Mount Marapi has erupted 170 times. Until Monday morning, April 29, 2024, at 06.00 WIB, Mount Marapi remains on Alert status (Level III). This indicates that a lot of landslide material due to volcanic eruptions has accumulated around the peak and upper slopes, which at any time can cause rain-induced lava floods. Related to the activities of Mount Marapi, a map of hazard-prone areas has been issued, including rivers that originate from Mount Marapi which are susceptible to rain-induced lava floods. The research was carried out by identifying river network patterns, hydrological characteristics, river morphology, and land use changes. The river network was analyzed using the Digital Elevation Model (DEM) from ASTER GDEM with a resolution of 8 m. Field validation for the river network was carried out using GPS Mapping at the Xakapa location. The hydrological and hydraulic profiles of the watershed were modeled using HEC-geoHMS and HEC-geoRAS to map the relationship between rainfall intensity, river discharge, and water level elevation along the river. From the modeling results, it can be seen that the rainfall intensity that has the potential to cause flooding is 142 mm/hour, using HEC-GeoHMS with a discharge of 1818 m3/second with a rainfall time of 6 hours causing a flood height of 0.81 m at an elevation of 379.9 with a wet cross-sectional area of ​​471 m2 in Xakapa.